Autoavaliação do desempenho acadêmico e trapaça: Contribuições dos valores e do jeitinho brasileiro - Moura, Hysla Magalhães de (2016)
This work aimed to propose an explanatory model of self-evaluation of academic performance from the academic cheating, human values and the Brazilian way. For this, two studies were conducted. In Study 1, as well as validation of cheating measures aimed to meet the relationships established with the self-evaluation of academic performance, so that it could propose an explanatory model. Therefore, it was decided to divide this study into three parts: Psychometric properties, Correlation and Explanatory Model. For Exploratory Factor Analysis of academic cheating measures participated 212 students with an average age of 16 years. The results showed bifatorias structures with acceptable reliability indicators EAT (Cronbach's alpha = 0.85 in the first factor; alpha = 0.79 Cronbrach the second factor) and EMT (Cronbach's alpha = 0.84 in the first factor, Alfa of Cronbrach = 0.708 in the second factor). Later, there was the Confirmatory Factor Analysis which included the participation of 229 students with an average age of 16 years. The findings showed that bifatoriais structures EAT (eg, GFI = 0.90, RMSEA = 0.07) and EMT (eg, GFI = 0.90, RMSEA = 0.05) are acceptable. Finally, for the realization of the Pearson correlation and the explanatory model, regrouped the entire sample used, so that it had the participation of 441 high school students. For the realization of the latter analysis, we used the following instruments: Basic Values Questionnaire (QVB), Trickery Admission Scale (EAT), Trickery Motivation Scale (EMT), Self-Assessment Scale of Academic Performance (EADA) and questionátio sociodemographic. The results emerge that cheating is positively related to the realization values and experimentation, while is negatively related to the normative value. While there has not been a significant relationship between cheating and interactive value, it was decided to include it in the model try to come view the theoretical framework. Furthermore, it was found that academic cheating is negatively related to the self-evaluation of academic performance. Still, in Study 1 was proposed and tested an explanatory model, relying on academic cheating and human values in their personal and social guidelines, as independent variables, while the self-evaluation of academic performance assumed role criterion variable. Soon, the fit indices demonstrated that the explanatory model is acceptable (eg GFI = 0.95, RMSEA = 0.11). In the Study 2 aimed to test an alternative model, so we reapplied the structure found in Study 1, adding the variable Brazilian way. The study included 205 students with a mean age of 24 years, which applied the same instruments used in the previous study, adding the Brazilian Jeitinho Scale (EJB). The findings emerge that this latest model showed better fit indexes than the model previously found (eg GFI = 0.94, RMSEA = 0.07). Trust to have contributed to the literature in the area by providing a better understanding of the factors which explain the self-evaluation of academic performance.